Response of Growth and Yield of Semi-dwarf XV heat to Phosphorus and Nitrogen Fertilizers - YOUSEF, M. E.; SGAIER, K.; EL-SHARKAWY, M. A. (The Libyan Journal of Agriculture, 2023)
The response of the semi-dwarf wheat cultivar *Sidi Misri I’ to both phosphorus and nitrogen fertilizers was studied in a field experiment on the sandy soil of Tripoli. Libya. The vegetative growth, as indicated by the studied parameters, and the grain yield and its components were significantly enhanced by the addition of phosphorus before planting. Postemergence nitrogen application up to 120 kg N/ha significantly increased the production of grains as well as straw. Excess nitrogen, beyond 120 kg N/ha, did not significantly increase the grain or straw production. Most of the grain yield components behaved similarly.